What a Difference a Mate Makes - Hromatko, Ivana; Tadinac, Meri; Prizmić, Helena (2006)
Numerous findings suggest that female preferences for certain features of male face vary during menstrual cycle. Similarly, it has been shown that women's commitment to their current relationships changes during menstrual cycle. The aim of this study was to explore whether women who are currently in a romantic relationship differ in their ratings of male facial attractiveness from single women, in different phases of menstrual cycle. Two groups of women (in a relationship vs. single) rated the attractiveness of two sets of male faces (normal vs. symmetrical). ANOVA showed significant relationship x cycle phase x symmetry interaction: women in a relationship gave higher ratings of attractiveness for both normal and symmetrical faces in luteal compared to early follicular phase of the cycle, while single women showed the opposite pattern. The results are interpreted in terms of plasticity of hormone mediated adaptive design.
Projekt MZOS
ENG